P16-specific DNA methylation by engineered zinc finger methyltransferase inactivates gene transcription and promotes cancer metastasis. Issue 1 (December 2015) - Cui, Chenghua; Gan, Ying; Gu, Liankun; Wilson, James; Liu, Zhaojun; Zhang, Baozhen; Deng, Dajun
Abstract Background P16 DNA methylation is well known to be the most frequent event in cancer development. It has been reported that genetic inactivation ofP16 drives cancer growth and metastasis, however, whetherP16 DNA methylation is truly a driver in cancer metastasis remains unknown. Results AP16 -specific DNA methyltransferase (P16-dnmt ) expression vector is designed using aP16 promoter-specific engineered zinc finger protein fused with the catalytic domain ofdnmt3a .P16-dnmt transfection significantly decreasesP16 promoter activity, induces complete methylation ofP16 CpG islands, and inactivatesP16 transcription in the HEK293T cell line. The P16-Dnmt coding fragment is integrated into an expression controllable vector and used to induceP16 -specific DNA methylation in GES-1 and BGC823 cell lines. Transwell assays show enhanced migration and invasion of these cancer cells followingP16 -specific DNA methylation. Such effects are not observed in theP16 mutant A549 cell line. These results are confirmed using an experimental mouse pneumonic metastasis model. Moreover, enforced overexpression ofP16 in these cells reverses the migration phenotype. Increased levels of RB phosphorylation and NFκB subunitP65 expression are also seen followingP16 -specific methylation and might further contribute to cancer metastasis. Conclusion P16 methylation could directly inactivate gene transcription and drive cancer metastasis.